Prevalence and factors associated with burnout among healthcare providers in Malaysia: a web-based cross-sectional study - Ching, Siew-Mooi; Cheong, Ai Theng; Yee, Anne; Thurasamy, Ramayah; Lim, Poh Ying; Ismail, Irmi Zarina; Lee, Kai Wei; Taher, Sri Wahyu; Ramachandran, Vasudevan (Springer, 2023)
Background: This study aimed to assess the determinants of burnout among healthcare providers in the primary care setting.